Stereotactic body radiotherapy (SBRT) for high-risk central pulmonary metastases - Lischalk, Jonathan W. (Radiat Oncol, 2016)
BACKGROUND AND PURPOSE: Radiotherapy of central lung tumors carries a higher risk of treatment-related toxicity and local failure. In the era of aggressive oligometastic management the exploration of the proper dose-fractionation for metastatic central lung tumors is essential. MATERIALS AND METHODS: Patients diagnosed with high-risk metastatic lesions of the central pulmonary tree comprised this single-institutional retrospective analysis. “High-risk” central pulmonary lesions were defined as those with abutment and/or invasion of the mainstem bronchus. All patients were treated using the CyberKnife SBRT system in 5 fractions to a total dose of 35 or 40 Gy. RESULTS: Twenty patients were treated from 2008 to 2011 at Georgetown University Hospital. At a median follow up of 19 months, 1-year Kaplan-Meier local control and overall survival was 70 and 75 %, respectively. Late grade 2 or higher atelectasis was the most common treatment-related toxicity and was significantly associated with maximum dose to the mainstem bronchus. Gross endobronchial involvement was associated with significantly lower overall survival. CONCLUSIONS: Five-fraction SBRT to a total dose of 35 or 40 Gy appears to be a safe and effective management strategy for high-risk central pulmonary metastatic lesions, though care should be taken to limit the maximum point dose to the mainstem bronchus.